A Model of the Air Rise Caused by the Water Vapor Condensation and its Numerical Computation - Ghomrani, S.; Marín-Antuña, J.; Fujita-Yashima, H. (Revista Cubana de Física, 2015)
We propose a system of equations to describe the development of the air rise caused by the water vapor condensation latent heat in a vertical cylinder of 10 km of height. The calculus results show a very fast development of the rising flow and its stabilization due to the friction of the droplets given by the water vapor condensation in the air.